2022
DOI: 10.1007/s00394-022-02862-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and health behaviour predictors of the weight gain during the COVID-19 pandemic

Abstract: Purpose This study aims to examine the effects of the COVID-19 pandemic on the body weight, nutritional habits, physical activity, and food consumption of adults living in Turkey and evaluate the effects of changes in these health behaviours on body weight. Methods A cross-sectional study was conducted with an online questionnaire. Data were collected through social media platforms using the snowball sampling method. A self-reported questionnaire included socio-demographic information, anthropometric data, die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…In a study conducted during the first 10 weeks of lockdown in Turkey, 35% of participants gained weight [ 31 ]. Additionally, a different study including the first 40 weeks of lockdown in Turkey showed that 58.5% of the participant gained weight [ 32 ]. It was determined that individuals who were already overweight and obese at the beginning of the pandemic gained more weight during the lockdown periods [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted during the first 10 weeks of lockdown in Turkey, 35% of participants gained weight [ 31 ]. Additionally, a different study including the first 40 weeks of lockdown in Turkey showed that 58.5% of the participant gained weight [ 32 ]. It was determined that individuals who were already overweight and obese at the beginning of the pandemic gained more weight during the lockdown periods [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study show that a lack of physical activity is an important risk factor for weight gain. In addition, other studies have shown that this situation is a major risk factor for weight gain [ 18 , 32 , 40 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The World Obesity Atlas (2022), published by the World Obesity Federation, predicts that 1 in 5 women and 1 in 7 men will be living with obesity by 2030, that correspond to one billion of people worldwide (World Obesity Atlas, 2022). Moreover, the global coronavirus disease 2019 pandemic and the consequent social restriction measures significantly changed individuals' body weight, physical activities, daily routines and eating habits (Ali Malik et al, 2022; Schneider et al, 2022), leading to an increase in eating disorders and obesity (Rodgers et al, 2020; Sideli et al, 2021; Urhan & Okut Aysin, 2022). The WHO criteria to diagnose obesity is the body mass index (BMI) that considers overweight a person with a BMI ≥ 25, while obese a person with a BMI ≥ 30 (World Health Organization, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…6,20,21 In a recent study, it was determined that physical activity was negatively affected at all levels and sedentary time was increased by 28% during the COVID-19 home confinement.6 In addition, in a recent study conducted in Turkey, the result that physical activity decreased by 69.5% during the pandemic period compared to before shows parallelism with our study. 22 In the present study, the ratio of participants who spent more than five hours per day on screens was by 77.8%. In our study, we also evaluated the time spent on the screen for entertainment and time except outside of work / homework / lessons as "leisure screen time".…”
Section: Discussionmentioning
confidence: 38%